Lower diastolic blood pressure in healthy subjects with vitamin K deficiency: a preliminary cross-sectional study - Nowak, Jan Krzysztof; Wykrętowicz, Andrzej; Krzyżanowska, Patrycja; Górna, Agnieszka; Tobolski, Jarosław; Mądry, Edyta; Walkowiak, Jarosław (Journal of Medical Science, 2016)
Introduction. There is a growing body of evidence for the role of vitamin K in cardiovascular health. As a cofactor of carboxylation of the matrix Gla protein it prevents arterial calcification. However, the data on the relationship between vitamin K status and the blood pressure are scarce, and particularly so in persons without the burden of cardiovascular risk factors. Material and Methods. We performed a pilot cross-sectional study, in which we hypothesized that vitamin K deficiency is associated with a higher blood pressure in young, healthy people. The concentration of protein induced by vitamin K absence-II (PIVKA-II) larger than 2 ng/mL was chosen as a proxy for vitamin K deficiency; it was assessed in serum using ELISA. Blood pressure was measured using a validated, automated oscillometric monitor in triplicate. Results. Twenty-three healthy subjects were enrolled (16 female; mean age 21.3 ± 1.6 years; body mass index 20.6 ± 2.4 kg/m2). The diastolic blood pressure (DBP) was lower in vitamin K-deficient subjects (58 ± 9 vs. 67 ± 5 mmHg, p = 0.01). The mean arterial blood pressure also differed (75 ± 9 vs. 83 ± 6, p = 0.02). PIVKA-II levels correlated with DBP only (Pearson’s R = -0.41, p < 0.05; Spearman’s ? ns.). Stepwise regression identified PIVKA-II concentrations as the only independent parameter associated with DBP (adjusted R2 = 13.1%; PIVKA-II: ß = -0.41; 95%CI -1.87-(-0.00098), t = -2.08, p < 0.05). Conclusions. The relationship between vitamin K deficiency and low DBP in young adults should be investigated further.